Niefinansowa perspektywa oceny w controllingu operacyjnym zakładów opieki zdrowotnej - Hass-Symotiuk, Maria; Mućko, Przemysław (Nonfinancial Assessment Perspectives of Operational Controlling in Health Care Organisations, 2007)
The paper is an analysis of external performance assessment systems for the purposes of implementing nonfinancial perspectives in operational controlling of health care organisations. As a result a tentative framework of performance metrics is proposed that consists of two dimensions. First is based on modern analysis of health systems (resources-processes-results). The second classifies metrics according to the aims of health systems.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 187-193